Aquinas, prudence, and proactive parenting: The "Treatise" applied. - McCabe, Joseph. (University of Ottawa (Canada), 1996)
This dissertation is on prudence and its role in child-rearing. More specifically, it is on how Thomas Aquina's Treatise on Prudence (S.T. IIa IIae QQ 47-56) can with profit be used to help parents today in the task of raising their children well. It is the author's conviction that Aquinas has a unique and important contribution to make to the contemporary debate on 'parenting', so-called, and the dissertation is a defense of that conviction. The paper is divided into three Parts, with each Part consisting of two chapters. The overall logical structure of the paper is that of chain argument which runs as follows. Employing the modern notion of 'proactivity' as a framework within which to speak of child-rearing practices, it is argued that: If proactive parent, then practical, provident, and equitable; If practical, provident, and equitable, then prudent; If proactive parent, then prudent. The thesis is that: It is not possible to be a proactive parent without the intellectual virtue of prudence. Each Part of the paper is dedicated respectively to one of the three qualities mentioned: practicality, providence, and equitability. Proactivity is a comprehensive theory of effective living; it is an approach to life and to problem-solving which has its origins in the fields of business and motivational psychology. Its principal proponent is the immensely popular author, lecturer, and leadership specialist, Dr. Stephen R. Covey. The use made of the notion of proactivity in the paper is twofold. First, in particular, it is used to focus the discussion of prudence and its role in conscientious parenting. The author noticed several fundamental and undeniable similarities between the notions of proactivity and prudence and has sought to exploit these similarities as a way of better understanding what it means to be an effective parent and to raise children well. Second, in general, the notion of proactivity is used to re-enter into the modern debate on child-rearing the figure of Thomas Aquinas. Parallel to the debate concerning public education, there arose a debate as to the 'private education', the upbringing, that children receive from their parents at home. And this debate--about which parenting style is most effective in raising children of responsible character--while certainly more focussed and closer to resolution today, is by no means overwith. It is into this debate that the author attempts to re-enter Thomas Aquinas and his Treatise on Prudence: under the auspices, that is, of the theory of 'proactivity'. (Abstract shortened by UMI.)
Keywords: Philosophy.